Investigation of the Microstructure of Disordered, Non‐graphitic Carbons by an Advanced Analysis Method for Wide‐Angle X‐ray Scattering12. Issue 15 (28th July 2014) - Faber, Kristin; Badaczewski, Felix; Ruland, Wilhelm; Smarsly, Bernd M.
Abstract The analysis of the wide‐angle X‐ray scattering (WAXS) data of non‐graphitic carbons is challenging due to the broad and overlapped (hk)‐ and (00l)‐reflections. A recently developed advanced analysis method developed by Ruland and Smarsly allows for the fitting of the WAXS data by a continuous model function, providing a detailed insight into the sp2‐carbon microstructure. Obtaining parameters like the graphene layer extent La, the average stack height Lc and disorder effects permits the quantification of microstructural features. Firstly, this publication gives a brief review over historical und recent developments regarding the evaluation of the WAXS of disordered carbons. Secondly, the applicability of this algorithm to carbon samples possessing a substantial degree of disorder is tested by investigating activated carbons, heat treated coal tar pitch and furfuryl alcohol. It is seen that several structural parameters are determined with reasonable accuracy and thereby the influence of the precursor and the temperature on the resulting carbon microstructure is identified. The decrease in disorder within the 2D graphene lattice and in the stacking of the layers at higher synthesis temperatures is quantified. Moreover, this study reveals that the graphene layer extent La is only about a few nanometers in size, showing that typical non‐graphitic carbons used for diverse applications possess quite small dimensions of graphene stacks.